COMMUNICATION STRATEGY OF THE AGILITY TRANSFORMATION COMPANY IN BUSINESS NETWORKING - Vashty, Shinta Qayla; Suminar, Jenny Ratna; Arifin, Hadi Suprapto (Universitas Swadaya Gunung Jati, 2025)
Networking is a critical strategy for business growth, yet specific methods for attracting and retaining clients often need to be better understood. This research addresses this gap by investigating Agility Transformation’s (AT) successful networking use to expand its business. The study aims to reveal how AT effectively develops and utilizes business networks to enhance client acquisition and retention, focusing on their strategic communication methods. The research employs a qualitative methodologies within a case study framework. Data were collected through in-depth interviews and detailed analysis of AT’s marketing frameworks and networking strategies. The findings demonstrate that AT utilizes marketing models, such as funnel and flywheel frameworks, to monitor client behavior and refine acquisition strategies. AT empathizes with clients at the awareness and discovery stages of the marketing funnel and engages clients throughout the flywheel. The company effectively uses various communication channels—including interpersonal, group, and public methods—and highlights attributes like open-mindedness, humility, proactivity, and personal alignment. To sustain client loyalty, AT offers ongoing training, shares relevant information and updates, and maintains active interaction on social media platforms. Agility Transformation’s networking strategy integrates modern marketing frameworks with strategic communication techniques. The company’s focus on the early stages of the marketing funnel and proactive client engagement significantly contribute to its success in acquiring and retaining clients. This study offers practical insights for businesses on optimizing networking strategies through contemporary marketing models and proactive communication. Theoretically, it enhances the understanding of how specific networking techniques and client engagement strategies can drive business growth.